2021
DOI: 10.1007/s43630-021-00041-x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the ability of low-level laser irradiation to reduce myonecrosis and increase Myogenin transcription after Bothrops jararacussu envenomation

Abstract: Envenoming caused by snakebites is a very important neglected tropical disease worldwide. The myotoxic phospholipases present in the bothropic venom disrupt the sarcolemma and compromise the mechanisms of energy production, leading to myonecrosis. Photobiomodulation therapy (PBMT) has been used as an effective tool to treat diverse cases of injuries, such as snake venom-induced myonecrosis. Based on that, the aim of this study was to analyze the effects of PBMT through lowlevel laser irradiation (904 nm) on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 73 publications
1
1
0
Order By: Relevance
“…The treatments lead to an advanced differentiation in the dystrophic muscle, by the down-regulation of MyoD levels and the up-regulation of myogenin levels. These data are in agreement with previous studies, which demonstrated improved myogenin expression in the muscle of the envenomation murine model due to the Bothrops jararacussu snake venom after PBMT [ 49 ] and modulation of the myogenic regulatory factors after multiple LEDT wavelengths [ 28 ]. In addition, we also identified the down-regulation of MHC-fast levels and up-regulation of MHC-slow levels after LEDT and IDE treatment.…”
Section: Discussionsupporting
confidence: 93%
“…The treatments lead to an advanced differentiation in the dystrophic muscle, by the down-regulation of MyoD levels and the up-regulation of myogenin levels. These data are in agreement with previous studies, which demonstrated improved myogenin expression in the muscle of the envenomation murine model due to the Bothrops jararacussu snake venom after PBMT [ 49 ] and modulation of the myogenic regulatory factors after multiple LEDT wavelengths [ 28 ]. In addition, we also identified the down-regulation of MHC-fast levels and up-regulation of MHC-slow levels after LEDT and IDE treatment.…”
Section: Discussionsupporting
confidence: 93%
“…21 This plethora of biological activities results in numerous therapeutic benefits beyond application to brain disorders. In fact, different preclinical studies suggest the applicability of PBM-induced biological effects to wound healing, 22 muscle regeneration, [23][24][25] and neuropathic pain, 26,27 among others. PBM has also been used to treat acute stroke, traumatic brain injury, 28 and several neurological and affective disorders, including MDD.…”
Section: Light Interactions With Biological Tissues: a Basis For Phot...mentioning
confidence: 99%
“…Para tais medidas, as imagens foram previamente calibradas com auxílio da ferramenta "set scale" a partir da barra de calibração de 20 µm. Uma vez identificados os pixels de interesse, foi utilizada a ferramenta "analyze particles" [120]. Vale ressaltar que as análises do número e área de fibras com núcleos centralizados foram realizadas às cegas.…”
Section: Ensaios Histológicosunclassified